2020
DOI: 10.1002/psp.2366
|View full text |Cite
|
Sign up to set email alerts
|

Social insurance participation and urban settlement intentions of China's floating population

Abstract: Since the expansion of social insurance to migrants and the abolition of unequal regulations and controls related to the rural-urban migrants in recent years, increasing attention has been paid to the determinants of migrants' settlement intentions. Using the 2016 National Floating Population Dynamics Monitoring Survey (NFPDMS), this study examines the associations between migrants' urban social welfare participation and their settlement intentions, including long-term settlement intention and transfer of one'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 65 publications
0
18
0
Order By: Relevance
“…Several studies have emphasized the role of non-economic factors in settlement intentions, such as social networks and social stress [ 30 , 31 , 32 , 33 ]. Sociological theory suggests that migration could be considered a dynamic social process that depends primarily on sociocultural factors [ 10 , 34 , 35 , 36 ]. By strengthening social ties with local residents, migrants are likely to settle as they expand their access to information, improve their chances of homeownership, and accumulate social capital.…”
Section: Research Background and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have emphasized the role of non-economic factors in settlement intentions, such as social networks and social stress [ 30 , 31 , 32 , 33 ]. Sociological theory suggests that migration could be considered a dynamic social process that depends primarily on sociocultural factors [ 10 , 34 , 35 , 36 ]. By strengthening social ties with local residents, migrants are likely to settle as they expand their access to information, improve their chances of homeownership, and accumulate social capital.…”
Section: Research Background and Literature Reviewmentioning
confidence: 99%
“…Rural migrants who have higher expectations of a convenient urban life, expect to provide better education for their children, and having relatives living in the same cities they are more willing to settle down [ 39 ]. Migrants who have social insurance have higher settlement intentions than those who have not [ 35 ], and they are more likely to settle down in cities with a large population and good climate conditions [ 35 , 40 ]. Previous studies have also investigated the impact of household demographic and socioeconomic characteristics on individuals’ settlement intentions.…”
Section: Research Background and Literature Reviewmentioning
confidence: 99%
“…Some studies have examined the impacts of access to employment‐related citizenship rights on migrants' settlement decision making (Huang et al, 2020; Yang & Li, 2017; Yu & Cheng, 2017). Using Migrants Dynamic Survey data in 2011, Wang and Zhao (2015) found that signing formal labour contract and access to social insurance drive migrants' intention of transferring hukou to the place of destination.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yu and Cheng (2017) also evidenced that both the employed and unemployed migrants are driven to achieve long‐term permanent residence via the access to medical insurance at the urban destination. The long‐term settlement intention and having a hukou transfer intention have increased by 12.6% and 2.9%, respectively, for one additional insurance coverage that migrants received (Huang et al, 2020). While the effects have been largely positive, there are some different voices.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation